2013
DOI: 10.14232/analecta.2013.1-2.16-21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of change of the colour parameters of paprika powder with different added oleoresin

Abstract: The instrumental colour measurement isn’t used in course of the making and the qualification of the paprika powder, although the colour is the most important sense property of its. Paprika is also used as a natural food colour. The colour of paprika powder is very important too, because the consumer concludes its colouring power based on its colour. The colouring power is determined by quality and quantity of colouring agent of paprika squarely. The colour of the powder is influenced by its particle size, oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The more yellow color could be attributed to the additional spice paprika seeds which increased the ratio of the yellow particles in the milled product. In addition, the spice paprika seeds are the main source of the oil content in the paprika powder and Horváth and Hodúr () found that the lightness ( L *) of paprika powders decreased with an increasing added oil content. The sun‐dried sample group had the darkest ( L * = 31.18–31.22), reddest (hab = 41.28–41.84), and the least saturated (Cab = 47.04–47.78) color compared to the Hungarian origin Szegedi‐20 paprika powder products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more yellow color could be attributed to the additional spice paprika seeds which increased the ratio of the yellow particles in the milled product. In addition, the spice paprika seeds are the main source of the oil content in the paprika powder and Horváth and Hodúr () found that the lightness ( L *) of paprika powders decreased with an increasing added oil content. The sun‐dried sample group had the darkest ( L * = 31.18–31.22), reddest (hab = 41.28–41.84), and the least saturated (Cab = 47.04–47.78) color compared to the Hungarian origin Szegedi‐20 paprika powder products.…”
Section: Resultsmentioning
confidence: 99%
“…The more yellow color could be attributed to the additional spice paprika seeds which increased the ratio of the yellow particles in the milled product. In addition, the spice paprika seeds are the main source of the oil content in the paprika powder and Horváth and Hodúr (2011) Table 3 presents the calculated difference in color parameters between the initial sample and after 3-, 6-, 9-, and 12month storage. The study by Horváth (2007) demonstrated that if the ΔE * ab > 1.5, the color difference between two paprika powders can be visually distinguished.…”
Section: Re Sults and Discussionmentioning
confidence: 99%